The associations among co-morbidity, cardiac geometries and mechanics in hospitalized heart failure with or without preserved ejection fraction - Chi-In Lo; Yau-Huei Lai; Sheng-Nan Chang; Jen-Yuan Kuo; Ya-Ching Hsieh; Bernard E. Bulwer; Chung-Lieh Hung; Hung-I Yeh (Clinical and Experimental Hypertension, 2017)
Background: The associations among chronic health conditions, ventricular geometric alterations or cardiac contractile mechanics in different phenotypes heart failure (HF) remain largely unexplored. Methods: We studied 438 consecutive hospitalized patients (mean age: 64.9 ± 16.6 years, 52.5% female) with or without clinical evidence of HF. We examined the associations among clinical co-morbidities, LV geometries and systolic mechanics in terms of global myocardial strains. Results: Increasing clinical co-morbidities was associated with greater LV mass, worse longitudinal deformations and higher proportion of admission with HF diagnosis, which was more pronounced in HFpEF (from 6.4% to 40.7%, X2 < 0.001). The independent association between co-morbidity burden and longitudinal functional decay remained unchanged after adjusting for age and sex for all admissions and in HFpEF (Coef: 0.82 & 0.71, SE: 0.13 & 0.21, both p≤0.001). By using co-morbidity scores, the area under receiver operating characteristic curves (AUROC) in identifying HFpEF was 0.71 (95% CI: 0.65 to 0.77), 0.64 (95% CI: 0.58 to 0.71) for HFrEF and 0.72 for both (95% CI: 0.67 to 0.77). Co-morbidity burden superimposed on LV mass index and LV filling pressure (E/E’) further expanded the AUROC significantly in diagnosing both types HF (c-statistics from 0.73 to 0.81, p for ΔAUROC: 0.0012). Conclusion: Chronic health conditions in the admission population were associated with unfavorable cardiac remodeling, impair cardiac contractile mechanics and further added significantly incremental value in HF diagnosis. Our data suggested the potentiality for better cardiac function by controlling baseline co-morbidities in hospitalized HF patients, especially HFpEF. Abbreviations: CAD: coronary artery disease; CKD: chronic kidney disease; DT: deceleration time; eGFR: Estimated glomerular filtration rate; HF: heart failure; IVRT: iso-volumic relaxation time; LV: left ventricular; LVEF: left ventricular ejection fraction; RWT: relative wall thickness; TDI: Tissue Doppler imaging